2019
DOI: 10.1016/j.cviu.2019.07.006
|View full text |Cite
|
Sign up to set email alerts
|

Exploring weight symmetry in deep neural networks

Abstract: We propose to impose symmetry in neural network parameters to improve parameter usage and make use of dedicated convolution and matrix multiplication routines. Due to significant reduction in the number of parameters as a result of the symmetry constraints, one would expect a dramatic drop in accuracy. Surprisingly, we show that this is not the case, and, depending on network size, symmetry can have little or no negative effect on network accuracy, especially in deep overparameterized networks. We propose seve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 23 publications
0
7
0
Order By: Relevance
“…The symmetry of neural network weights was studied in [13]. It was shown that weights located at the same distance from the centre of the network can be equal or inversely proportional.…”
Section: Related Workmentioning
confidence: 99%
“…The symmetry of neural network weights was studied in [13]. It was shown that weights located at the same distance from the centre of the network can be equal or inversely proportional.…”
Section: Related Workmentioning
confidence: 99%
“…CNNs can capture richer and more complex characteristics by adjusting the network depth. However, the vanishing gradient [47] problem makes network training more difficult. The network can collect more fine-grained features by adjusting its width.…”
Section: Figure 3: Architecture Of the Efficientnet-b0mentioning
confidence: 99%
“…Therefore, the entire non-local spectral correlation prediction does not take up a lot of calculation and memory. After this operation, we also add weight symmetrization [36] to obtain a symmetric correlation matrix C s . The weight symmetrization can be briefly expressed by a linear operator [36].…”
Section: The Non-local Spatial-spectral Attention Modulementioning
confidence: 99%
“…After this operation, we also add weight symmetrization [36] to obtain a symmetric correlation matrix C s . The weight symmetrization can be briefly expressed by a linear operator [36]. Subsequently, the feature map x is subjected to 1 × 1 convolution processing and then multiplication with C s .…”
Section: The Non-local Spatial-spectral Attention Modulementioning
confidence: 99%